Application of Various Organic Matter and Incubation Period to change some Chemical Properties of Ultisol Soil - Pasnel Sianturi; Fauzi Jamal; MMB Damanik (Universitas Sumatera Utara, 2018)
The objective of this study is to determine the effect of some organic matter and incubation period on the pH, C-organic, total-P, total-N and K-exchange on Ultisol. This research conducted in Soil Science Laboratory, Faculty of Agriculture, University of North Sumatra. This study used completely randomized design which consist of two factors with three replications. Factor I: organic matter (B) ie : B0 (without organic matter), B1 (compost of Tithonia diversifolia 10g/pot), B2 (compost of durian skin 10g/pot), B3 (compost of oil palm empty fruit bunch 10g/pot), B4 (chicken manure 10g/pot), B5 (compost of Tithonia diversifolia 5g/pot + chicken manure 5g/pot), (compost of durian skin 5g/pot + chicken manure 5g/pot), B7 (compost of oil palm empty fruit bunch 5g/pot + chicken manure 5g/pot) and factor II : the incubation period (I), ie : I1 (three weeks incubation), I2 (four weeks incubation). The results showed that application compost of durian skin, Tithonia diversifolia, and compost of oil palm empty fruit bunch significantly increased soil pH, C-organic, total-P, total-N and K-exchange. The combination between compost of durian skin and chicken manure significantly increased Ultisol soil pH. Keywords : Incubation, Organic matter, Total-P, Ultisol